Contra o direito de não ter cuidado: ventilações ameríndias para resistir ao (no) Antropoceno - Alysson Amorim Mendes da Silveira (2018)
The research discusses the connections of modernity and its naturalist ontology with the emergence of what has been recognized as a new geological epoch: the Anthropocene. The work seeks to demonstrate how this era, marked by ecological imbalances of anthropic cause, is the product of a paradigm where the relations of man with his environment are constituted based on a right of not to have care. Using anthropology, the research seeks to explore concepts produced from the intellectual pragmatics of Amerindian peoples proposing an alternative paradigm where the care, important role of the law neglected by modernity, re-play its role.